Design and Development of Ariesta Hotel Reservation Information System Based Website Using Waterfall Method - Elsa Benolon; Yoseph Pius Kurniawan Kelen; Siprianus Septian Manek (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2026)
The limitations of the manual reservation system at Hotel Ariesta Kefamenanu result in inefficient information delivery, a high risk of recording errors, and potential double bookings. This study aims to develop a web-based reservation information system to improve service efficiency and data accuracy. The Waterfall method is applied to ensure a structured and systematic development process in accordance with user requirements. The system is developed using the Bootstrap framework to provide a responsive interface accessible across multiple devices. The results indicate that the proposed system reduces the reservation processing time and minimizes data recording errors compared to the previous manual system. In addition, the system improves the accuracy of reservation data management and enables real-time access to hotel information, including room types, facilities, and pricing. The implementation of this system also enhances promotional effectiveness and expands customer reach through continuous online accessibility. Therefore, the developed system serves as an effective solution to support digital transformation and improve operational performance at Hotel Ariesta Kefamenanu.